2017
DOI: 10.1016/j.trb.2016.12.010
|View full text |Cite
|
Sign up to set email alerts
|

On the stability of stationary states in general road networks

Abstract: In (Jin, 2015), with a discrete map in critical demand levels, it was proved that there exist stationary states for the kinematic wave model of general road networks with constant origin demands, route choice proportions, and destination supplies. In this study we further examine the stability property of stationary states with the same map, and the results will help us to understand the long-term trend of a network traffic system. We first review a network kinematic wave model and properties of stationary sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 20 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Drivers can also demonstrate varied driving behaviours, such as maintaining gaps when following a leading car, applying brakes frequently, and changing lanes continually, complicating the overall traffic dynamics. Similarly, heterogeneity is a common feature of real-world traffic flow [ 121 ]. The distinctions between homogeneous and heterogeneous traffic systems, frequently referred to as mixed traffic systems, are primarily attributable to the diverse operational and performance characteristics of vehicles.…”
Section: Vissim Application Literature Reviewmentioning
confidence: 99%
“…Drivers can also demonstrate varied driving behaviours, such as maintaining gaps when following a leading car, applying brakes frequently, and changing lanes continually, complicating the overall traffic dynamics. Similarly, heterogeneity is a common feature of real-world traffic flow [ 121 ]. The distinctions between homogeneous and heterogeneous traffic systems, frequently referred to as mixed traffic systems, are primarily attributable to the diverse operational and performance characteristics of vehicles.…”
Section: Vissim Application Literature Reviewmentioning
confidence: 99%
“…In the stationary state, the traffic flow states of the junction are studied (21), and the fundamental diagram of a specific lane and lane flow distribution are calibrated (22,23). In recent research by Jin (24)(25)(26), both observations and theoretical studies have confirmed that the traffic states are relatively stationary during peak period on a road network, and the stability and existence of stationary states in general road networks have been proved within the framework of kinematic wave theories.…”
mentioning
confidence: 99%